2016
DOI: 10.1186/s12936-015-1074-8
|View full text |Cite
|
Sign up to set email alerts
|

A malaria risk map of Kinshasa, Democratic Republic of Congo

Abstract: BackgroundIn Kinshasa, malaria remains a major public health problem but its spatial epidemiology has not been assessed for decades now. The city’s growth and transformation, as well as recent control measures, call for an update. To identify highly exposed communities and areas where control measures are less critically needed, detailed risk maps are required to target control and optimize resource allocation.MethodsIn 2009 (end of the dry season) and 2011 (end of the rainy season), two cross-sectional survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 19 publications
7
72
0
8
Order By: Relevance
“…As an attempt to identify factors explaining high malaria rates in northern Ghana, Monroe et al found that under-usage of LLINs at times when they could confer maximum protection as well as a variety of outdoor night-time activities, including outdoor sleeping were factors that could have potentially contributed to high rates of malaria in that setting [32]. In this study, the prevalence of anaemia was high and consistent with findings of other researchers [26], however additional factors common in this setting such as malnutrition [17] and sickle cell anaemia [33] play a role in the occurrence of this condition.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As an attempt to identify factors explaining high malaria rates in northern Ghana, Monroe et al found that under-usage of LLINs at times when they could confer maximum protection as well as a variety of outdoor night-time activities, including outdoor sleeping were factors that could have potentially contributed to high rates of malaria in that setting [32]. In this study, the prevalence of anaemia was high and consistent with findings of other researchers [26], however additional factors common in this setting such as malnutrition [17] and sickle cell anaemia [33] play a role in the occurrence of this condition.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, in this study, the same pattern was observed even in households possessing sufficient numbers of LLIN to cover all residents, suggesting a behavioural gap in LLIN use among older children and adolescents. The lower LLIN use rate obviously put this age group at higher risk of malaria prevalence as reported in other studies [26, 27]. …”
Section: Discussionmentioning
confidence: 54%
“…As it happens, Kinshasa has been subject to one of the world's most detailed mapping of malaria incidence across a major urban setting, which could inform mitigation measures in other cities, especially in sub‐Saharan Africa . This study confirmed the widely observed phenomenon that malaria is less prevalent in central or downtown districts where breeding grounds for the vector, here the Anopheles gambiae mosquito, are restricted, but much more so in densely populated suburbs or peripheral areas.…”
Section: A Lack Of Sciencesupporting
confidence: 70%
“…Wealth is clearly linked to better living conditions, including access to food as well as better health. In Kinshasa, for example, away from the areas highlighted, prevalence of malaria and anaemia is significantly higher (Ferrari et al 2016); a reflection of more socioeconomically deprived zones.…”
Section: Discussionmentioning
confidence: 98%